The Experiences of Blended Training Implementation from Nutrition Goes to School (NGTS) Program in Indonesia - Februhartanty, Judhiastuty; Pramesthi, Indriya Laras; Kusuma, Sari; Shinta, Dewi; Dewi, Aisyah Nurcita; Ermayani, Evi; Hidayat, Ahmad Thohir; Oka, A A Sagung Indriani; Andari, Izzati Hayu; Wiradnyani, Luh Ade Ari (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to evaluate the implementation of a blended training for school teachers on adolescent health and nutrition. The training objective was to improve teachers’ knowledge, as well as their capacity to develop and implement action plans on school-based health and nutrition programs. Adolescents continue to face nutrition problems closely linked with poor eating behaviours and lack of physical activity. School has been identified as an effective venue for improving these problems. Many teachers’ training programs were reported on increasing the teachers’ roles in school health and nutrition program, but studies utilizing a blended training is lacking. This study used pre-post intervention with mixed methods design. The participants of this blended training were secondary school teachers who enrolled in a five-phase Nutrition Goes to School (NGTS) training on school-based nutrition promotion program, comprising in-service learning and on-the-job training for ten months. The participants decreased throughout the training to 114 participants completed the whole training. Out of 114 participants, 25 (22%) passed this NGTS blended training. Participants’ knowledge on health and nutrition improved as shown in pre-test median score of 60 and post-test median score of 80 (p<0.001). The final assignment on developing action plans showed a relatively good quality of engagement based on the participants’ understanding on the NGTS program, their resources, and their ability to manage challenges. Blended training with long duration but accompanied with technical assistance can provide added value in understanding the process of the NGTS program implementation and school-based health and nutrition program in general. However, the high attrition rate should be improved by facilitating more varied and engaging activities as part of the technical assistance in the future training program.